CONTROL OF BURROWING NEMATODE INFECTION OF MUSA SPP AS AFFECTED BY PLANTING DEPTH AND POULTRY MANURE RATES IN MGBAKWU, ANAMBRA STATE. - N.k., Ndulue; P, C, O, Onugbolu; Gloria, Ekemezie; Chukwuka , Nwajikwa (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Yield and control of burrowing nematode disease of Musa spp as affected by planting depth and poultry manure rates as soil organic amendment were studied in a 3x3x2 factorial experiment in a randomized complete block design with six replicates. The organic amendments were applied in two Musa spp. The poultry manure was apllied at the rate of 0 t/ha, 5 t/ha and 10 t/ha while the planting depth were 30cm, 45cm, and 60cm respectively. The 0 t/ha of poultry manure served as the control. The result of the analysis showed that burrowing nematode population density and its infection on Musa spp varied among the organic amendment applied. The same was true for yield and other yield components. Planting depth of 60cm and 10 t/ha poultry manure efficiently controlled the activities of burrowing nematode and therefore improved yield.